SISTEM INFORMASI PENJUALAN OBAT-OBATAN PT.SAN PRIMA SEJATI BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract-This final assignment of  researching about construction of information system sale of medicines PT. San Prima Sejati web based branch of Semarang. The problems are how to plan and build system of information sale of medicines in PT. San Prima Sejati that will can gives  various supporting information for process selling to consumen and for facilitate consumen in buying product. Method of development system that used is prototype model. software implementation that used are Dreamweaver, Photoshop with PHP and MySql. From  this final assignment had been result an application  information system sale of medicines web based that can used by sales PT. San Prima Sejati to facilitate selling system to consumen  medicines store, apotic or etc. For completing can add features according to feedback from salesman to facilitate their jobs in take befenits from  that application. Key words: Web, Selling, Medicines, Information Sysetm